Environmental health hazard of arsenic on epididymis and ductus deferens in male Black Bengal Goats (Journal of the Bangladesh Agricultural University, 2014)
Histomorphological changes of epididymis and ductus deferens in male Black Bengal goat due to arsenic were studied. A total of 12 male Black Bengal goats, in which 6 were collected from arsenic affected areas of Mymensingh district and another 6 were collected from hill tracts of Chittagong which were arsenic free.The goats were sacrificed by piercing carotid artery and the samples (Epididymis and Ductus deferens) were collected immediately. Samples were prepared and stained with haematoxylin and eosin stain technique to study the histology under light microscope. In the morphological study, measurement of length, width, breadth and weight of epididymis and ductus deferens were observed. The gross study revealed that there were slight variations in the gross morphology of epididymis and ductus deferens of arsenic affected Black Bengal goat, but this variation was statistically insignificant. In the histological study, arsenic affected goat showing increased thickness of epididymal covering (P